Candida albicans Heat Shock Proteins and Hsps-Associated Signaling Pathways as Potential Antifungal Targets - Gong, Ying; Li, Tao; Yu, Cuixiang; Sun, Shujuan (Frontiers in Cellular and Infection Microbiology, 2017)
In recent decades, the incidence of invasive fungal infections has increased notably. Candida albicans (C. albicans), a common opportunistic fungal pathogen that dwells on human mucosal surfaces, can cause fungal infections, especially in immunocompromised and high-risk surgical patients. In addition, the wide use of antifungal agents has likely contributed to resistance of C. albicans to traditional antifungal drugs, increasing the difficulty of treatment. Thus, it is urgent to identify novel antifungal drugs to cope with C. albicans infections. Heat shock proteins (Hsps) exist in most organisms and are expressed in response to thermal stress. In C. albicans, Hsps control basic physiological activities or virulence via interaction with a variety of diverse regulators of cellular signaling pathways. Moreover, it has been demonstrated that Hsps confer drug resistance to C. albicans. Many studies have shown that disrupting the normal functions of C. albicans Hsps inhibits fungal growth or reverses the tolerance of C. albicans to traditional antifungal drugs. Here, we review known functions of the diverse Hsps family, Hsps-associated intracellular signaling pathways and potential antifungal targets based on these pathways in C. albicans. We hope this review will aid in revealing potential new roles of C. albicans Hsps in addition to canonical heat stress adaptions and provide more insight into identifying potential novel antifungal targets.